Reframing EFL Classrooms Students’ Perspectives on Translanguaging as a Pedagogical Strategy in Indonesian Senior High School - Cahyanti, Agnes Dewi; Dharmawan, Yanuarius Yanu (Indonesian Journal of Teaching and Learning, 2025)
Translanguaging has emerged as a powerful pedagogical approach in multilingual EFL classrooms, especially in culturally and linguistically diverse contexts. This study aimed to explore the perspectives of tenth-grade students at SMA Gajah Mada Bandar Lampung towards the use of translanguaging strategies in their English classes. The research employed a qualitative case study design, involving 30 participants selected through purposive sampling. Data were collected using classroom observations, semi-structured interviews, and a structured questionnaire. The analysis revealed that students frequently resorted to their first language (L1) to alleviate anxiety and enhance comprehension, especially when encountering difficulties with English (L2). The majority expressed positive attitudes towards translanguaging, believing that the integration of L1 alongside L2 helped them engage more actively, understand instructions better, and participate with greater confidence. However, a small number of students were hesitant, citing concerns over overdependence on L1. Teachers’ reactions also played a significant role in shaping students’ comfort, as those who positively acknowledged L1 use were more likely to foster inclusive participation. The findings suggest that translanguaging supports learners’ emotional, cognitive, and linguistic development when strategically integrated by teachers. This study offers new insight into how translanguaging not only aids language acquisition but also reduces classroom anxiety. It contributes to the growing body of research advocating for flexible language practices in EFL settings. The results are significant for EFL educators, curriculum developers, and policy-makers seeking to create inclusive and supportive language learning environments in multilingual classrooms.